If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 3) + -1(2x + -1) = 3 Reorder the terms: 5(3 + x) + -1(2x + -1) = 3 (3 * 5 + x * 5) + -1(2x + -1) = 3 (15 + 5x) + -1(2x + -1) = 3 Reorder the terms: 15 + 5x + -1(-1 + 2x) = 3 15 + 5x + (-1 * -1 + 2x * -1) = 3 15 + 5x + (1 + -2x) = 3 Reorder the terms: 15 + 1 + 5x + -2x = 3 Combine like terms: 15 + 1 = 16 16 + 5x + -2x = 3 Combine like terms: 5x + -2x = 3x 16 + 3x = 3 Solving 16 + 3x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 3x = 3 + -16 Combine like terms: 16 + -16 = 0 0 + 3x = 3 + -16 3x = 3 + -16 Combine like terms: 3 + -16 = -13 3x = -13 Divide each side by '3'. x = -4.333333333 Simplifying x = -4.333333333
| 0.35x+.05(12-x)=.10(-48) | | -8=2+9m-1 | | 4x-9x=39 | | d-4.9=18.8 | | -[7x-(3x+10)]=-3-[4(2x-4)-2x] | | 3(3n+3)=9(6n+5)8 | | 6(x-5)=-48 | | 0.5x-0.3(2-x)=4.6 | | -4=a+6 | | 9x^2+3x-3xy-y=0 | | 5x^2-2x^2+9x^2+x^2=0 | | .01x+.10x+.25(35-2x)=4.07 | | 5+3x+2x+7=2 | | 4p^3+36p=0 | | 42-x=19 | | c-4=13.7 | | 6x*x+7x-20=0 | | n-6=-10 | | 0=x^2-25x+144 | | 9(5+x)=15(10+x) | | 4x-(9-3x)=18x-1 | | w=4+8 | | 15-j+5j+2=-14 | | p=4+8 | | -4(x+4)=5-(-4) | | 2(-18)+3=3(-18)+7 | | -5(x+7)=5-(-1) | | 4x=3(49-x) | | 5+h=-6 | | .67x=5 | | 17.50+4p=53.50 | | 7-5m=45 |